2013
DOI: 10.1149/2.023312jes
|View full text |Cite
|
Sign up to set email alerts
|

Sidewall Texture and Microstructure of iPVD Copper Seed in Narrow Damascene Trenches

Abstract: Impurities incorporated into copper during electrochemical deposition have long been postulated to inhibit grain growth in narrow interconnects. In this article we examine an alternative possible origin for the microstructural differences observed between narrow and wide lines. Specifically, the iPVD Cu seed layers in wide (1 μm) and narrow (70 nm) lines differ significantly in microstructure and texture, as analyzed by transmission electron microscopy and electron diffraction. The seed in the wide lines has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
(59 reference statements)
2
4
0
Order By: Relevance
“…10 Several publications, however, have suggested that in narrow lines, high dislocation density, seed layer texture, and minimization of the Cu-Ta interfacial energy cause coarsening of grains in the trenches prior to the overburden. 8,11,12 In this work, TEM analysis of samples during and after the transformation is presented supporting the trench-initiated recrystallization hypothesis, and goes further to show that the microstructure inside the trenches is stable well before the transformation in the overburden is complete.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…10 Several publications, however, have suggested that in narrow lines, high dislocation density, seed layer texture, and minimization of the Cu-Ta interfacial energy cause coarsening of grains in the trenches prior to the overburden. 8,11,12 In this work, TEM analysis of samples during and after the transformation is presented supporting the trench-initiated recrystallization hypothesis, and goes further to show that the microstructure inside the trenches is stable well before the transformation in the overburden is complete.…”
supporting
confidence: 72%
“…23 In our previous work, 11 we showed that the seed texture in narrow lines is random, while the field is still 111-textured, as would be expected in films. After plating, the overburden above the trenches is also 111-textured, despite the random orientations found on the sidewall seed.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Primarily, prior works (Oh et al 2013;Heryanto et al 2011;Weide-zaage 2012;Wu et al 2010;O Brien 2013;Hommel et al 2002;Paik et al 2004) have considered crystalline copper and isotropic material properties for reliability simulations. A clear dependance between the copper microstructure in nanoscale interconnects, void formation kinetics, and electromigration statistics has been established through experiments (Cao et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The texture of the Cu seed on the sidewall of the narrow trenches was recently found different from the ones in wide trenches, which could potentially explain the difference in grain growth. 10 In addition, an increased incorporation of nonmetallic impurities (C, O, S, Cl) in the Cu narrow lines during electroplating has been long observed. 9,11,12 A higher impurity level was known to hinder the Cu grain growth in blanket films [13][14][15][16] and thus could potentially account for the difficulty of grain grown in narrow lines as well.…”
mentioning
confidence: 99%